2016
DOI: 10.1016/j.jacep.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mortality Associated With Quadripolar Compared to Bipolar Left Ventricular Leads in Cardiac Resynchronization Therapy

Abstract: In this observational study of CRT-D devices, use of a quadripolar, compared to a bipolar LV lead, was associated with a reduction in LV lead deactivation, replacement, and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 25 publications
3
25
2
Order By: Relevance
“…Outcomes following CRT implantation with quadripolar compared with bipolar leads have been reported from several previous studies with differing designs [8], [9], [10]. As with the current study from Rijal, in all previous reports, quadripolar leads were found to have a higher freedom from implant failure and/or need for early reintervention for dislodgment or PNS than bipolor leads.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Outcomes following CRT implantation with quadripolar compared with bipolar leads have been reported from several previous studies with differing designs [8], [9], [10]. As with the current study from Rijal, in all previous reports, quadripolar leads were found to have a higher freedom from implant failure and/or need for early reintervention for dislodgment or PNS than bipolor leads.…”
supporting
confidence: 77%
“…additionally found that quadripolar CRT implants were associated with a lower rate of subsequent hospitalization – and therefore lower medical costs – than bipolar CRT implants [9]. Finally, a study including all U.S. patients from a single manufacturer's database including over 23,000 patients (roughly three-fourths treated with quadripolar leads) further reported that patients receiving quadripolar leads had slightly lower mortality (5.04 vs. 6.45 deaths per 100 patient-years, hazard ratio 0.77, p < 0.001) than those receiving bipolar leads [10].…”
mentioning
confidence: 99%
“…A recent retrospective study comparing QUAD with bipolar leads showed no difference in survival at 12 months (mean follow‐up 256 days for QUAD) . In contrast, a US‐wide study based on data from device implant records and telemonitoring showed that CRT‐D using QUAD was associated with a better survival than CRT‐D using bipolar leads . Observational data from 3 centers in the United Kingdom showed similar findings …”
Section: Discussionmentioning
confidence: 90%
“…Some observational studies have suggested that CRT‐D using QUAD programmed to single‐site LV pacing also improves survival . These findings, however, are not consistent, and there is uncertainty as to whether they also apply to CRT‐P.…”
Section: Introductionmentioning
confidence: 99%
“…Biventricular pacing, achieved by placing a left ventricular (LV) lead through a coronary venous branch in addition to a conventional RV lead, has been proven to prolong survival and improve symptoms and LV ejection fraction (EF) in patients with HF with widened QRS complexes (corresponding to ventricular depolarization) on the electrocardiogram (ECG) 4446 . Given that approximately one-third of patients do not show improvements in functional capacity or EF with CRT, novel, multipoint pacing modalities have been developed 47 to pace the left ventricle at multiple points 48 . Randomized clinical trials to compare the effects of bipolar versus quadripolar leads in patients with CRT are ongoing 44 .…”
Section: Electronic Pacemakersmentioning
confidence: 99%